382 Addressing racial and ethnic disparities in drowning rates in the United States. (20th November 2022) - Clemens, Tessa; Moreland, Briana; Lee, Robin
Abstract : Background: Drowning death rates decreased by 32% in the U.S. since 1990. However, rates remain high among Non-Hispanic American Indian or Alaska Native (AI/AN) and Non-Hispanic Black or African-American (Black) persons. Methods: National Vital Statistics System death certificate data from 1999–2019 were used to calculate unintentional drowning death rates and disparity rate ratios (RRs), using Non-Hispanic White (White) persons as the reference, for persons aged ≤29 years. Pilot programs were developed to evaluate and improve access to swim skills interventions in communities at increased risk of drowning. Results: Drowning death rates were 2.0 times higher among AI/AN persons and 1.5 times higher among Black persons. Disparities in drowning death rates between Black and White persons increased from 2005 to 2019. Racial/ethnic disparities were present in all settings and most pronounced in swimming pool deaths; the highest RRs occurred among Black youth 10–14 years (7.6), 15–19 years (5.6), and 5–9 years (4.4). Pilot programs leveraged community partnerships to engage underserved children in 22 communities in swim skills training. Conclusion: Racial/ethnic disparities differed by setting, and applicable drowning prevention strategies differ by setting; however, basic swimming and water safety skills can be beneficial in all settings. CDC is working with national organizations to pilot and evaluate basic swimming and water safety skills training programs in communities at increased risk of drowning. Learning outcomes: Understand persistent racial/ethnic disparities in U.S. drowning rates. Understand successes and challenges of implementing basic swim skills training in communities at increased risk of drowning.